Strategi Manajemen Konflik dalam Lingkungan Lembaga Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine in depth the strategies of conflict management within Islamic educational institutions. The research employs a qualitative approach with a literature review design, drawing on data from books, scholarly journal articles, and relevant academic documents published within the last ten years. The findings indicate that conflicts in Islamic educational institutions are multidimensional, encompassing interpersonal, organizational, value-based, role-related, and interest-based conflicts. Conflict demonstrates an ambivalent impact, as it can be destructive when not properly managed, leading to decreased performance, disrupted professional relationships, and weakened learning quality. However, conflict also holds constructive potential when managed effectively, as it can stimulate innovation, enhance communication, and improve decision-making processes. The strategies identified include collaboration, compromise, accommodation, competition, and avoidance, with their application depending on the specific context of the conflict. Among these, a collaborative approach is considered the most effective, as it promotes mutually beneficial solutions. Furthermore, the integration of Islamic values such as consultation (shura), justice, and reconciliation (islah) plays a crucial role in conflict management. Therefore, effective conflict management can contribute to the development of a harmonious, productive educational environment oriented toward character building. Keywords: conflict management, Islamic educational institutions, conflict strategies, Islamic values, educational organization